The Impact of Cash holdings on Firm Performance: An Empirical Investigation of US Firms - Cheng, Na (2017)
Cash holding is a major factor affecting the company performance and financial constraint is also important when we assess the companies’ financial behaviours. This study firstly investigates the relationship between firm performance, corporate cash holdings and financial constraints by using data of 11848 public US enterprises from 2006 to 2016 on the baseline model. This paper then empirically tests the existence of a nonlinear relationship between corporate performance and cash holdings and analyses this relation under different financial conditions. The results show a nonlinear association between firm performance and cash holdings in both more financially constrained companies and less financially constrained ones, which fits in with the trade-off theory. Moreover, this study shows evidence that cash is more valuable in firms with financial constraints than those that are free from such problems.